2010
DOI: 10.1085/jgp.201010468
|View full text |Cite
|
Sign up to set email alerts
|

Massive calcium–activated endocytosis without involvement of classical endocytic proteins

Abstract: We describe rapid massive endocytosis (MEND) of >50% of the plasmalemma in baby hamster kidney (BHK) and HEK293 cells in response to large Ca transients. Constitutively expressed Na/Ca exchangers (NCX1) are used to generate Ca transients, whereas capacitance recording and a membrane tracer dye, FM 4–64, are used to monitor endocytosis. With high cytoplasmic adenosine triphosphate (ATP; >5 mM), Ca influx causes exocytosis followed by MEND. Without ATP, Ca transients cause only exocytosis. MEND can then be initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
105
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 82 publications
(145 reference statements)
9
105
3
Order By: Relevance
“…1f). Previous reports about this subject are contrasting, some agree with our observation [20,41,45], but others refer no effect on C m [43,50]. Such dissimilar results could be explained due to specific cell type and/or the particular conditions established to induce depletion of plasma membrane cholesterol (e.g., MBCD concentration, incubation time, and temperature).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…1f). Previous reports about this subject are contrasting, some agree with our observation [20,41,45], but others refer no effect on C m [43,50]. Such dissimilar results could be explained due to specific cell type and/or the particular conditions established to induce depletion of plasma membrane cholesterol (e.g., MBCD concentration, incubation time, and temperature).…”
Section: Discussioncontrasting
confidence: 49%
“…In our experimental conditions, the observed decrease of C m could be explained if cholesterol depletion (1) induces endocytosis, (2) increases the thickness of plasma membrane, (3) decreases the dielectric constant value of the hydrophobic bilayer core, or (4) changes the mechanoelastic properties of the plasma membrane and/or its interaction with the cytoskeleton components. The first possibility is not supported by early studies where cholesterol depletion significantly inhibited clathrin-dependent [42] or clathrin-independent Ca 2+ -activated massive endocytosis [20]. An increased internalization of the surface membrane triggered by cholesterol depletion involving changes in membrane raft-cytoskeleton interactions, however, remains as a possibility [45].…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, recent electrophysiological studies also reported massive endocytosis in cells subjected to large intracellular Ca 2+ transients, or exposed to bacterial sphingomyelinase 48, 49 . This rapid endocytic process, designated as MEND (massive endocytosis), did not involve the actin cytoskeleton or the endocytosis-regulatory proteins clathrin and dynamin 48 .…”
Section: Sphingomyelinase Emerges As a Major Regulator Of Lesion Remomentioning
confidence: 99%
“…This rapid endocytic process, designated as MEND (massive endocytosis), did not involve the actin cytoskeleton or the endocytosis-regulatory proteins clathrin and dynamin 48 . These findings are similar to that observed for the sphingomyelinase-dependent endocytic process that mediates plasma membrane repair, which is also dynamin-independent 9, 16, 22 .…”
Section: Sphingomyelinase Emerges As a Major Regulator Of Lesion Remomentioning
confidence: 99%
See 1 more Smart Citation